Penerapan Reward dan Punishment di SMA Negeri Bareng Kab. Jombang sebagai Upaya Meningkatkan Kedisiplinan Guru dalam Kehadiran Mengajar di Kelas - Ahmad (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2019)
Improving the quality of learning in schools depends on several factors. A very important factor is the application of school culture towards quality improvement. School culture that must be maintained is one of disciplinary problems, including the discipline of teachers in attendance in class in the teaching and learning process. The purpose of this study was to improve teacher discipline in the presence of teaching in the classroom through the application of Reward and Punishment measures in SMA Negeri Bareng, Jombang. This research was conducted in two cycles. The results of the study in the first cycle of discipline in the presence of teachers in teaching in late classes less than 10 minutes was 24.3%, which means that the results have not met the predetermined indicator of success of 75%. In the second cycle the discipline of the presence of teachers in teaching in late class less than 10 minutes was 78.4%, it shows that in the second cycle, the discipline of teacher attendance in the classroom in the learning process increased and fulfilled the set indicators of 75%. Based on the results of the research obtained it can be concluded that to improve the discipline of teacher attendance in the classroom in learning activities can be done by applying Reward and Punishment to the teacher